How Social Communications Influence Advertising Perception and Response in Online Communities? - Zeng, Fue; Tao, Ran; Yang, Yanwu; Xie, Tingting (Frontiers in Psychology, 2017)
This research aims to explore how social communications of online communities affect users’ perception and responses toward social media advertising. We developed a conceptual model based on the social bond theory (SBT), encapsulating nine constructs and ten hypothesis extracted from the extant social media advertising literature. Our research outcome proves that social communications can effectively boost users’ behaviors to be in accordance with an online social community, thus facilitate their acceptance and responses toward social media advertising, with users’ group intention as an intervening factor. From an operational standpoint, it’s an effective way to build and maintain social bonds between users and the community by boosting social communications supporting fluent interpersonal communications. In addition, managers of an online community should elaborate on users’ group intentions to increase users’ advertising acceptance and response.